Msa: an R package for multiple sequence alignment. (26th August 2015) - Bodenhofer, Ulrich; Bonatesta, Enrico; Horejš-Kainrath, Christoph; Hochreiter, Sepp
Abstract : Summary: Although the R platform and the add-on packages of the Bioconductor project are widely used in bioinformatics, the standard task of multiple sequence alignment has been neglected so far. The msa package, for the first time, provides a unified R interface to the popular multiple sequence alignment algorithms ClustalW, ClustalOmega and MUSCLE. The package requires no additional software and runs on all major platforms. Moreover, the msa package provides an R interface to the powerful package shade which allows for flexible and customizable plotting of multiple sequence alignments. Availability and implementation: msa is available via the Bioconductor project: http://bioconductor.org/packages/release/bioc/html/msa.html . Further information and the R code of the example presented in this paper are available at http://www.bioinf.jku.at/software/msa/ . Contact: bodenhofer@bioinf.jku.at or msa@bioinf.jku.at